The business of choice : marketing to consumers' instincts - Wilcox, Matthew (Person Education, 2015)
Reshape Consumer Behavior by Making Your Brand the Instinctive, Intuitive, Easy Choice! • Discover powerful new ways to simplify and guide consumer decisions • Gain actionable insights into social influence, how people plan, and how they interpret the past • Leverage surprising advances in neuroscience, evolutionary biology, and the behavioral and social sciences Whatever your marketing or behavioral objective, you'll be far more successful if you know how humans choose. Human intuitions and cognitive mechanisms have evolved over millions of years, but only now are marketers beginning to understand their impact on people's decisions. The Business of Choice helps you apply new scientific insights to make your brand or target behavior the easiest, most instinctive choice. Matthew Willcox integrates the latest research advances with his own extensive enterprise marketing experience at FCB's Institute of Decision Making. Willcox explains why we humans often seem so irrational, how marketers can leverage the same evolutionary factors that helped humans prosper as a species, how to make decisions simpler for your consumers, and how to make them feel good about their choices, so they keep coming back for more!